Implementation of Dakon-themed game media: Encourage curiosity 21st century in primary school - Arih Afra Inayah; Enny Zubaidah (Intelektual Pustaka Media Utama, 2020)
Thematic learning, especially thematic integrative, basically requires the optimization of the use of varied learning media so that it will help students in understanding the concepts of material which are abstract. Therefore, the use of learning media is important in learning. This study aims to reveal: 1) the eligibility of Dakon-themed game media on the topic “Where I Live”, and 2) the effectiveness of Dakon-themed game media in improving the curiosity of grade IV students of elementary school. This development research was conducted in Kulonprogo Regency, Special Region of Yogyakarta, Indonesia and developed the media according to the 10 steps developed by Borg and Gall. The testing subjects consisted of 9 students in the initial field trial phase, 34 students in the main field trial and 74 students in the operational field trial which were divided into experimental and control groups. The data collection was trough tests, expert rating scale and response questionnaire. The effectiveness of the media of media on the theme of topic Where I live in improving the curiosity of analytical students with N-gain, and t-test with an alpha level of 0.05.The results reveal that: (1) the developed Dakon-theme on the topic Where I Live meets the eligibility criteria based on the results of the validation with very feasible criteria; and (2) the developed game is effective in improving curiosity of the fourth grade students of elementary schools.